2009
DOI: 10.1093/carcin/bgp232
|View full text |Cite
|
Sign up to set email alerts
|

The properties of tumor-initiating cells from a hepatocellular carcinoma patient's primary and recurrent tumor

Abstract: Hepatocellular carcinoma (HCC) is associated with a high morbidity and mortality due to its high rate of recurrence. However, little is known about the biological characteristics of recurrent HCC cells. A single patient's primary and recurrent HCC-derived cell lines, Hep-11 and Hep-12, respectively, were established by primary culture. These two cell lines have the same hepatitis B virus integration site and share many common amplifications and deletions, which suggest that they have the same clonal origin. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 42 publications
2
70
0
Order By: Relevance
“…The fact that most of the recurrent HCC-originated Hep-12 cells remain as TICs even with prolonged in vitro culture has led to the identification of a TIC population expressing the a2d1 subunit 29,30 . Here we developed a protocol by combining genome-wide miRNA profiling with softagar functional screening assay based on the Hep-12 cell line, to identify miRNAs that suppress the HCC TIC fate and have successfully identified a set of miRNAs, including four most effective miRNAs (let-7c, miR-200b, miR-222 and miR-424) that suppress the stemness and tumorigenicity of a2d1 þ HCC TICs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that most of the recurrent HCC-originated Hep-12 cells remain as TICs even with prolonged in vitro culture has led to the identification of a TIC population expressing the a2d1 subunit 29,30 . Here we developed a protocol by combining genome-wide miRNA profiling with softagar functional screening assay based on the Hep-12 cell line, to identify miRNAs that suppress the HCC TIC fate and have successfully identified a set of miRNAs, including four most effective miRNAs (let-7c, miR-200b, miR-222 and miR-424) that suppress the stemness and tumorigenicity of a2d1 þ HCC TICs.…”
Section: Discussionmentioning
confidence: 99%
“…Future work is needed to address the driving events in the a2d1 þ cell-induced HCC, especially how the four miRNAs are deregulated in the a2d1 þ HCC TICs. 29 . The Huh7, HepG2 and SMMC7721 cell lines were originated from Japan Society for the Promotion of Science (Tokyo, Japan), American Type Culture Collection (Manassas, VA) and the Second Military Medical University of China (Shanghai, China), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 More recently, NCAM was found in cancer-initiating stem cells of the liver. 41,42 We demonstrated that in HCC, NCAM, although present in several cancer cells, was significantly down-modulated and practically absent in stroma and in vessels, thus indicating that, contrarily in other cancers, 43,44 NCAM does not stain tumor vessels of HCC.…”
Section: Tgf-b1 Induces Vascular Abnormalities In Hccmentioning
confidence: 82%
“…Similarly, a 'CSC-TPC' phenotype with high aggressivity and tumorigenesis in animals, with markers of ESC (OCT4, SOX2 and NANOG) and with ALDH þ , ABCG2 þ , poly (ADP-ribose) polymerase þ and insulin-like growth factor-1 þ expressions displays the most competitive phenotype appearing in recurrent hepatocellular carcinoma but no special surface markers (Xu et al, 2010).…”
Section: Csc-tpc Biomarkersmentioning
confidence: 99%